Anti-hypertensive Effect of Cereal Antioxidant Ferulic Acid and Its Mechanism of Action - Alam, Md. Ashraful (Frontiers in Nutrition, 2019)
Abstract: Ferulic acid is a simple phenolic acid found mainly in cereals and grains, used as an antioxidant and food preservative. Recent evidence suggests that ferulic acid possess anti-inflammatory, anti-diabetic, anticancer and cardioprotective properties. Basic and clinical investigations also have implied that ferulic acid rich food may prevent hypertension. As a potent scavenger of free radicals (ROS, reactive oxygen species), ferulic acid attenuates oxidative stress, which leads to the benefit of blood-pressure reduction through improved endothelial function and nitric oxide bioavailability in the arterial vasculature. This review article focuses on the physiological and biochemical findings on this subject and highlights some remaining issues that merit further scientific and clinical exploration.